2010
DOI: 10.2353/ajpath.2010.090048
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to Mesenchymal Transition in Human Skin Wound Healing Is Induced by Tumor Necrosis Factor-α through Bone Morphogenic Protein-2

Abstract: Epithelial-mesenchymal transition (EMT), characterized by loss of epithelial adhesion and gain of mesenchymal features, is an important mechanism to empower epithelial cells into the motility that occurs during embryonic development and recurs in cancer and fibrosis. Whether and how EMT occurs in wound healing and fibrosis in human skin remains unknown. In this study we found that migrating epithelial cells in wound margins and deep epithelial ridges had gained mesenchymal features such as vimentin and FSP1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
186
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(200 citation statements)
references
References 30 publications
11
186
0
3
Order By: Relevance
“…Wound healing in skin has been studied extensively, and several critical molecular processes, such as an inflammatory response, EMT, and ECM remodeling, have been identified (20,21). Similar injury-healing processes were also observed in the heart tissues of our PTSD mouse model.…”
Section: Discussionsupporting
confidence: 54%
“…Wound healing in skin has been studied extensively, and several critical molecular processes, such as an inflammatory response, EMT, and ECM remodeling, have been identified (20,21). Similar injury-healing processes were also observed in the heart tissues of our PTSD mouse model.…”
Section: Discussionsupporting
confidence: 54%
“…This has recently been reported in human skin wound healing. A study using human skin tissues from acute wounds in the phase of re-epithelialisation found that migrating epithelial cells in wound margins and deep epithelial ridges gained mesenchymal features such as vimentin and FSP1 expression [2]. In vitro, tumour necrosis factor-α (TNF-α) induced expression of vimentin, FSP1, and matrix metalloproteinases in normal human skin and primary keratinocytes and this was inhibited by BMP antagonists, suggesting that BMP mediates the TNF-α-induced EMT in human skin.…”
Section: Bmp Emt and Tissue Regenerationmentioning
confidence: 99%
“…It is well known that periods of EMT are necessary during development but can also occur during fibrosis and tumour progression. More recently, EMT-like processes have been described during tissue repair [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The autocrine/paracrine signaling of cytokines, such as EGF, TGF-␤, and TNF-␣, regulate EMT morphologic phases in keratinocytes (18,28,29). EGF family members are primary growth factors involved in re-epithelialization during cutaneous wound healing (30,31).…”
Section: Aberrant Glycosylation Of Egf-r Enhances Its Signaling In Gnmentioning
confidence: 99%
“…In adults, EMT, which is driven by the cytokine bath generated by tissue injury, mediates the production of fibroblasts during inflammation and wound healing (18 -20). Re-epithelialization in wound healing involves the motility or migration of epithelial cells, and the migrating epithelial cells in wound margins acquire mesenchymal features and follow early stages of EMT (18).…”
mentioning
confidence: 99%